2015
DOI: 10.1167/iovs.15-16921
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Summation of Perimetric Stimuli in Early Glaucoma

Abstract: Temporal summation is altered in glaucoma. The stimulus duration and area of conventional SAP may be suboptimal for identifying early functional damage. Simultaneously modulating stimulus duration, area, and luminance during the examination may improve the diagnostic capability of SAP and expand the dynamic range of current instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
80
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(89 citation statements)
references
References 50 publications
8
80
1
Order By: Relevance
“…The results of this study support the proposition of Anderson that testing within complete spatial summation provides a mechanism to identify a larger threshold elevation in ocular disease. Both spatial and temporal aspects are important in threshold determination applicable to visual field testing . The following discussion focuses on spatial considerations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study support the proposition of Anderson that testing within complete spatial summation provides a mechanism to identify a larger threshold elevation in ocular disease. Both spatial and temporal aspects are important in threshold determination applicable to visual field testing . The following discussion focuses on spatial considerations.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods have also scaled for differences in foveal to peripheral sensitivity, or vary target size while maintaining target contrast constant (STP) . Scaling methods include using the cortical magnification factor; using the slope of the coefficient of summation (k1) for a Goldmann III target to calculate differential light sensitivity and determine the relationship with ganglion cell density; aligning target size with the critical area (Ac), derived from spatial summation studies of Ricco's law at different retinal eccentricities . Latham et al .…”
Section: Discussionmentioning
confidence: 99%
“…15,[28][29][30][31][32] Within the central 308 of the field of vision, at which threshold visual field tests are most commonly conducted, the GIII target often exceeds spatial summation area, particularly for the central test locations. 24,25 Given the importance of test size in relation to the Ac to the fidelity of visual sensitivity, 15,[28][29][30]32 we hypothesize that the GC structure-function relationship will improve and approach 1:1 positive correlation by altering the test size within complete spatial summation. Similarly, as the summation characteristic is known to change with the disease process, 28 comparisons of the structure-function relationship between normal and glaucomatous cohorts need to be conducted.…”
mentioning
confidence: 99%
“…From this equation, Ricco's law of spatial summation ( L.A n1 = k ) and Bloch's law of temporal summation ( L.t n2 = k ) can be derived . When n is equal to one, the test stimulus is operating within the critical area (Ac) or critical duration (Tc) of complete summation and there is a linear relationship between luminance and stimulus duration; outside of Tc or Ac, this relationship is non‐linear …”
Section: Test Parameters Used In Standard Automated Perimetrymentioning
confidence: 99%
“…Conversely, OCT imaging has been suggested to show more loss at the beginning but plateaus in advanced stages of disease due to the floor effect of its measurement technique (see Table 3 and Figure in Medeiros and colleagues). More recent studies have shown that equating for spatiotemporal summation characteristics can allow detection of functional losses in earlier stages of glaucoma . Simple modifications of test stimuli at different visual field test locations can specifically maximise defect detection, while maintaining the widest dynamic range of testing .…”
Section: The Problem Of Structure‐function Discordancementioning
confidence: 99%